Physicochemical Properties And Antioxidant Activity Of Green Grass Jelly Containing Sago Starch - Hasan, Nik Nur Hidayah Nik (Universiti Sains Malaysia, 2020)
Green grass jelly also called “Cincau hijau” is one of the popular traditional dessert in Asia country especially Indonesia. Normally it served with hot or chilled drinks together with a sweet base like fruit syrup, coconut milk and ice. Green grass jelly however exhibits very high syneresis during storage. Hence, in this study, sago starch at different concentrations (0, 5, 5.5, 6 and 6.5%) were added into the green grass jelly formulations to overcome the syneresis issues. Besides, effects of the sago starch on the physicochemical and antioxidant activity of the newly developed green grass jellies were analyzed. Formulated green grass jellies were analyzed for physicochemical analysis syneresis, colour, texture and antioxidant properties (total phenolic content (TPC) and antioxidant activity (2, 2-diphenyl-1-picrylhydrazyl free radical scavenging activity (DPPH-SA)). The value of syneresis decreased significantly (p<0.05) with increasing the sago starch concentration. As for the colour analysis, L* values which indicate the lightness were increased significantly (p<0.05) with increasing of sago starch concentrations. Besides, -a* value which indicate the greenness showed that jelly without addition of sago starch (control) was significantly different (p< 0.05) compared to those added with sago starch. This is probably due to gelatinization of starch granules occurred during the cooking process. Yellowness (b*) value of the jelly were significantly (p< 0.05) increase with increases in sago starch concentration.